Mental health first aid training for nursing students: a protocol for a pragmatic randomised controlled trial in a large university - Crawford, Gemma; Burns, Sharyn; Chih, Hui Jun; Hunt, Kristen; Tilley, Peter; Hallett, Jonathan; Coleman, K.; Smith, S. (BioMed Central Ltd., 2015)
BackgroundThe impact of mental health problems and disorders in Australia is significant. Mental health problems often start early and disproportionately affect young people. Poor adolescent mental health can predict educational achievement at school and educational and occupational attainment in adulthood. Many young people attend higher education and have been found to experience a range of mental health issues. The university setting therefore presents a unique opportunity to trial interventions to reduce the burden of mental health problems. Mental Health First Aid (MHFA) aims to train participants to recognise symptoms of mental health problems and assist an individual who may be experiencing a mental health crisis. Training nursing students in MHFA may increase mental health literacy and decrease stigma in the student population. This paper presents a protocol for a trial to examine the efficacy of the MHFA training for students studying nursing at a large university in Perth, Western Australia. Methods/DesignThis randomised controlled trial will follow the CONSORT guidelines. Participants will be randomly allocated to the intervention group (receiving a MHFA training course comprising two face to face 6.5 hour sessions run over two days during the intervention period) or a waitlisted control group (not receiving MHFA training during the study). The source population will be undergraduate nursing students at a large university located in Perth, Western Australia. Efficacy of the MHFA training will be assessed by following the intention-to-treat principle and repeated measures analysis. DiscussionGiven the known burden of mental health disorders among student populations, it is important universities consider effective strategies to address mental health issues. Providing MHFA training to students offers the advantage of increasing mental health literacy, among the student population. Further, students trained in MHFA are likely to utilise these skills in the broader community, when they graduate to the workforce. It is anticipated that this trial will demonstrate the scalability of MHFA in the university environment for pre-service nurses and that implementation of MHFA courses, with comprehensive evaluation, could yield positive improvements in the mental health literacy amongst this target group as well as other tertiary student groups. Trial registrationAustralian New Zealand Clinical Trials Registry ACTRN12614000861651